Protocol for a quasi-experimental, 950 county study examining implementation outcomes and mechanisms of Stepping Up, a national policy effort to improve mental health and substance use services for justice-involved individuals - Jennifer E. Johnson; Jill Viglione; Niloofar Ramezani; Alison E. Cuellar; Maji Hailemariam; Rochelle Rosen; Alex Breno; Faye S. Taxman (Implementation Science, 2021)
Abstract Background The criminal justice system is the largest provider of mental health services in the USA. Many jurisdictions are interested in reducing the use of the justice system for mental health problems. The national Stepping Up Initiative helps agencies within counties work together more effectively to reduce the number of individuals with mental illness in jails and to improve access to mental health services in the community. This study will compare Stepping Up counties to matched comparison counties over time to (1) examine the effectiveness of Stepping Up and (2) test hypothesized implementation mechanisms to inform multi-agency implementation efforts more broadly. Methods The study will survey 950 counties at baseline, 18 months, and 36 months in a quasi-experimental design comparing implementation mechanisms and outcomes between 475 Stepping Up counties and 475 matched comparison counties. Surveys will be sent to up to four respondents per county including administrators of jail, probation, community mental health services, and community substance use treatment services (3800 total respondents). We will examine whether Stepping Up counties show faster improvements in implementation outcomes (number of justice-involved clients receiving behavioral health services, number of behavioral health evidence-based practices and policies [EBPPs] available to justice-involved individuals, and resources for behavioral health EBPP for justice-involved individuals) than do matched comparison counties. We will also evaluate whether engagement of hypothesized mechanisms explains differences in implementation outcomes. Implementation target mechanisms include (1) use of and capacity for performance monitoring, (2) use and functioning of interagency teams, (3) common goals and mission across agencies, and (4) system integration (i.e., building an integrated system of care rather than adding one program or training). Finally, we will characterize implementation processes and critical incidents using survey responses and qualitative interviews. Discussion There are few rigorous, prospective studies examining implementation mechanisms and their relationship with behavioral health implementation outcomes in justice and associated community behavioral health settings. There is also limited understanding of implementation mechanisms that occur across systems with multiple goals. This study will describe implementation outcomes of Stepping Up and will elucidate target mechanisms that are effective in multi-goal, multi-agency systems.